2018 IEEE International Conference on Teaching, Assessment, and Learning for Engineering (TALE) 2018
DOI: 10.1109/tale.2018.8615407
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Sharing in Digital Learning Communities: A Comparative Review of Issues between Education and Industry

Abstract: Digital learning communities have become a focal point of organizational development. The education industry has begun to follow suit by using the same technologies to enhance the learning process through a deeper process of participation. These technological tools complement sound learning design to bring a wealth of benefits to students. These benefits are not without peril. New technological tools shift common issues of education into online environments. This article reviews recent implementations of digit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Relying on the good-Samaritan-style of motivation factors was not influential. As do the works of Alam et al (2009) and Jackson et al (2018), we found that a positively motivated employee will happily share knowledge with others. The positive influence of motivation is also supported in the works of Kankanhalli et al (2005) and Y. S. Choi (2000).…”
Section: Discussionmentioning
confidence: 69%
“…Relying on the good-Samaritan-style of motivation factors was not influential. As do the works of Alam et al (2009) and Jackson et al (2018), we found that a positively motivated employee will happily share knowledge with others. The positive influence of motivation is also supported in the works of Kankanhalli et al (2005) and Y. S. Choi (2000).…”
Section: Discussionmentioning
confidence: 69%
“…The problem of modernization of the educational services markets in the conditions of formation of Industry 4.0 is studied in a lot of fundamental and empirical works of modern scholars and experts, which include Bogoviz (2019), Jackson et al (2019), Kalolo (2019), Ma (2019), Papadakis et al (2018), Popkova (2017Popkova ( , 2019, Popkova and Sergi (2019), Sozinova (2019), Sukhodolov et al (2018) and Yakovenko et al (2019). At the same time, a gap in the accumulated knowledge on this topic is deficit of regional research, because of which regional specifics of modernization of the educational services markets in the conditions of formation of Industry 4.0 is poorly studied and not taken into account during management of this process.…”
Section: Methodsmentioning
confidence: 99%